The Profile of Urolithiasis Patient at Aeramo General Hospital: A Descriptive Research at Remote Area - Gore, Andreas Perdana Putra; Wibisono, Eric (Brawijaya Journal of Urology, 2025)
Introduction. Urolithiasis is the fourth leading cause of kidney failure in Indonesia. Indonesia does not have a comprehensive national profile for urolithiasis. This study aims to profile the urolithiasis patient at Aeramo General Hospital, East Nusa Tenggara. Methods. This study used a descriptive design, collecting data on urolithiasis patients from non-electronic medical records from October 2020 to May 2024. Results. A total of 80 patients with urolithiasis were included in this study, 44 with kidney stones, 33 with bladder stones, and 3 with both. The largest age group was 40–60 years (50%), with a male predominance (81.25%). Most were farmers (50%) with a high school education (35%). The majority of patients smoked (63.75%) and consumed alcohol (68.75%). The most common symptom was colic pain (67.5%). Abdominal ultrasound was the primary diagnostic modality (77%). Most kidney stones measured 1–2 cm (55%), and most bladder stones were >4 cm (47%). Forty-three patients underwent surgery, while 37 did not, primarily due to financial constraints (70.3%). Conclusion. The highest incidence of urolithiasis was found in men aged 40-60 years, predominantly farmers with a high school education. Kidney stones were most common, with sizes of 1-2 cm, while bladder stones were mostly >4 cm. Financial constraints were the primary reason for refusing surgery.